The foramen magnum and its contents : a magnetic resonance imaging study of the normal spatial relationships - Lotz, Jan Willem (Division of Anatomical Pathology, 2017)
The well-known neurological disturbances associated with caudal displacement of the cerebellar tonsils through the fora men magnum (Chiari malformation) have lead to many radiological studies of the region. With MRI, routine sagittal and parasagittal views of the craniovertebral junction have shown that the position of the cerebellar tonsils is variable, and in many otherwise healthy individuals, the inferior tonsillar margins lie within the fora men magnum itself. In some cases, this topography is associated with little signal from the surrounding cerebra-spinal fluid (CSF), indicating reduction of the cerebellomedullary cistern and, therefore, crowding of neural structures within the confines of the fora men. The objective of this study has been to examine the spatial relationship between the contents of the foramen magnum ie. the medulla and cerebellar tonsils, using a normal sample comprising 120 volunteers. Instead of the conventional measurements of distance, a ratio, the Foramen Magnum Index (FMI), has been determined, derived from the relative surface areas (pixels) of neural parenchyma and CSF, over axially and sagittaly-defined boundaries of the fora men. The FMI, with a 95th centile of 0.77, exhibits appropriate statistical correlation with tonsillar position below the level of the foramen, and is therefore considered specific. As a quantitative means of assessing the cerebellomedullary cistern, the FMI also identifies certain subjects whose tonsils are at the foramen, in whom the cistern is small with resultant neural crowding.